KEEFEKTIFAN MODEL TWO STAY TWO STRAY BERBANTU MEDIA RODA PINTAR MATEMATIKA TERHADAP HASIL BELAJAR - Novia Prinsa Anggarini; novia prinsa anggarini; Sumarno Sumarno; Ervina Eka Subekti (Universitas Ngudi Waluyo, 2019)
The purpose of this research is to know the effectiveness of Two Stay Two Stray model assisted media of smart mathematics wheel to hail to learn fourth grader of SD Negeri Plelen 02 Batang. This research is a quantitative research using one group pretest posttest design research design. The results of the test of learning showed that the results of learning results of students who use the Two Stay Two Stray model auxiliary media mathematical wheels reach a classical percentage of 92%. The posttest score of 76.20 and the minimum completeness criterion (KKM) 70, obtained by t = 8.64 with n = 25, and ttabel 1.710. So the calculation results are known 8.64> 1.710. Based on the test criteria when obtained t count> ttable is 8.64> 1.710 so H0 diterima. In conclusion Two Stay Two Stray model auxiliary media effective mathematics media to the results of the fourth grade students of SD Negeri Plelen 02 Batang.Keywords: Two Stay Two Stray models, math smart wheels, learning outcomesÂ